2015
DOI: 10.1037/pne0000017
|View full text |Cite
|
Sign up to set email alerts
|

Variation of 5-HTTLPR and deficits in emotion regulation: A pathway to risk?

Abstract: Genetic variation in the serotonergic system within the brain has been a significant focus of psychiatric research over the last several decades. In particular, the serotonin transporter (5-HTT) gene (SLC6A4) has been tied to early emotion processing biases. However, a clear understanding of how genetic variation of SLC6A4 may influence clinically salient emotional phenomena is still elusive. In this investigation, we focused on examining variation in the 5-HTT-linked polymorphic region (5-HTTLPR; including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…For example, Gilman and colleagues (2015) examined variation in the 5-HTTLPR and emotion responses to a task designed to spontaneously induce emotion regulation; they found that for individuals with two copies of the short allele of this gene, there was weakened downregulation of negative emotion, indicating that perhaps these individuals (relative to those without two copies of the short allele) are more vulnerable to affective disorders. In a separate study, Miu and colleagues (2013) found evidence for reappraisal as a mediator of the relationship between the 5-HTTLPR gene and social anxiety symptoms, such that individuals with two copies of the short allele reported increased social anxiety symptoms and decreased use of reappraisal.…”
Section: Emotion Regulation As a New Rdoc Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gilman and colleagues (2015) examined variation in the 5-HTTLPR and emotion responses to a task designed to spontaneously induce emotion regulation; they found that for individuals with two copies of the short allele of this gene, there was weakened downregulation of negative emotion, indicating that perhaps these individuals (relative to those without two copies of the short allele) are more vulnerable to affective disorders. In a separate study, Miu and colleagues (2013) found evidence for reappraisal as a mediator of the relationship between the 5-HTTLPR gene and social anxiety symptoms, such that individuals with two copies of the short allele reported increased social anxiety symptoms and decreased use of reappraisal.…”
Section: Emotion Regulation As a New Rdoc Domainmentioning
confidence: 99%
“…5-HTT=serotonin transporter gene; COMT=catechol-O-methyltransferase gene; PFC=prefrontal cortices; ACC=anterior cingulate cortex; EMG=electromyography; EEG=electroencephalogram; ERQ=Emotion Regulation Questionnaire; DERS = Difficulties in Emotion Regulation Scale; CERQ = Cognitive Emotion Regulation Questionnaire; ERI = Emotion Regulation Interview; ERP-R=Emotion Regulation Profile-Revised; EROS=Emotion Regulation of Others and Self; IERQ=Interpersonal Emotion Regulation Questionnaire; 1 (Gilman et al, 2015); 2 (Miu et al, 2013); 3 (Nikolova, Davis, & Hariri, 2014); 4 (Kim et al, 2011); 5 (Salgado-Pineda et al, 2005); 6 (Canli & Lesch, 2007); 7 (Outhred et al, 2015); 8 (Hariri & Holmes, 2006); 9 (Crockett et al, 2008); 10 (Quirin et al, 2011); 11 (Lam et al, 2009); 12 (Poon et al, this issue); 13 (Walker et al, 2013); 14 (Miller et al, 2005); 15 (Banks et al, 2007); 16 (Etkin & Schatzberg, 2011); 17 (Marusak et al, 2015); 18 (Buhle et al, 2014); 19 (Kohn et al, 2014); 20 (Ochsner et al, 2002); 21 (Etkin, Egner, Peraza, Kandel, & Hirsch, 2006b); 22 (Etkin et al, 2010); 23 (Etkin & Wager, 2007); 24 (Phillips et al, 2003); 25 (Gross, 1998a); 26 (Gross & Levenson, 1993); 27 (Mauss et al, 2007); 28 (Dan-Glauser & Gross, 2015); 29 (Roberts et al, 2008); 30 (Giuliani...…”
Section: Figurementioning
confidence: 99%
“…Indeed, some studies demonstrated a link between the S allele and a difficulty disengaging from emotional stimuli (Beevers, Marti, Lee et al . ; Beevers, Wells, Ellis, McGeary, ; Gilman, Latsko, Matt et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heightened emotional reactivity and deficits in emotion regulation in S allele carriers have been shown by Gilman et al . (). Kochanska, Philibert and Barry () using a longitudinal design showed that children who carried a short 5‐HTTLPR allele, developed poor regulatory capacities if they were insecurely attached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation